Uteroplacental Insufficiency Impairs Cholesterol Elimination in Adult Female Growth-Restricted Rat Offspring Fed a High-Fat Diet. (September 2019) - Zinkhan, Erin K.; Yu, Baifeng; McKnight, Robert
Uteroplacental insufficiency (UPI) causes intrauterine growth restriction (IUGR) and increases the risk of hypercholesterolemia and cardiovascular disease, which are leading causes of morbidity and mortality worldwide. Little is known about the mechanism through which UPI increases cholesterol. Hepatic Cholesterol 7 alpha-hydroxylase (Cyp7a1) is the rate-limiting and most highly regulated step of cholesterol catabolism to bile acids. Cholesterol 7 alpha-hydroxylase is regulated by transcription factor liver X receptor α (Lxrα) and by microRNA-122. We previously showed that microRNA-122 inhibition of Cyp7a1 translation decreased cholesterol catabolism to bile acids in female IUGR rats at the time of weaning. We hypothesized that UPI would increase cholesterol and microRNA-122 and decrease Cyp7a1 protein and hepatic bile acids in young adult female IUGR rats. To test our hypothesis, we used a rat model of IUGR induced by bilateral uterine artery ligation. Both control and IUGR offspring were exposed to a maternal high-fat diet from before conception through lactation, and all offspring were weaned to a high-fat diet on postnatal day 21. At postnatal day 60, IUGR female rats had increased total and low-density lipoprotein serum cholesterol and hepatic cholesterol, decreased Lxrα and Cyp7a1 protein, and decreased hepatic bile acids. Hepatic microRNA-122 was not changed by UPI. Our findings suggest that UPI decreased cholesterol catabolism to bile acids in young adult female rats through a mechanism independent of microRNA-122.